الانقسام المجتمعي كمحدد تفسيري لانهيار التسوية السياسية في اليمن وأثر ذلك على واقع مؤسسة الجيش - والي, فايزة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تستهدف الدراسة مناقشة أثر الانقسام المجتمعي المهيكل في تنظيمات سياسية واجتماعية، خصوصا في وقت الأزمات السياسية والأمنية؛ حيث يساهم في عرقلة التوصل لتسوية سياسية تحضي بقبول تلك التنظيمات السياسية والاجتماعية والنخبة الحاكمة، وذلك عبر لحظة فارقة في الأزمة تحدث خلل في ميزان القوى لصالح تنظيم معين، فتتوجه عملية التسوية نحو الانهيار، وتكون الدولة ومؤسساتها ككيان المتأثر بذلك خصوصا مؤسسة الجيش التي يعد تكوينها انعكاسا لذلك التعدد، ويتفاقم بفعل انهيار عملية التسوية، وهو الحاصل باليمن؛ حيث تحكمت تنظيمات اجتماعية في مسار التسوية، مما ساهم في انهيارها الدولة و مؤسسة الجيش The study aims to discuss the impact of the societal division in structured political and social organizations, especially at a time of political and security crises, as it contributes to obstructing a political settlement that requires the acceptance of those political and social organizations and the ruling elite, and that through a defining moment in the crisis, an imbalance of power occurs in favor of a specific organization The settlement process is directed towards collapse, so the state and its institutions as an entity affected by that, especially the army, whose formation is a reflection of that number and is aggravated by the collapse of the settlement process, which is happening in Yemen, where social organizations have controlled the course of the settlement and contributed to its collapse, what constituted a threat to the state and its institutions, especially the army institution